Evaluation of Indigenous Pichia kudriavzevii from cocoa fermentation for a probiotic candidate - Rahayu Wulan; Rika Indri Astuti; Yaya Rukayadi; Anja Meryandini (Society for Indonesian Biodiversity, 2021)
Abstract. Wulan R, Astuti RI, Rukayadi Y, Meryandini A. 2021. Evaluation of Indigenous Pichia kudriavzevii from cocoa fermentation for a probiotic candidate. Biodiversitas 22: 1317-1325. Currently, probiotics are becoming a concern along with a healthy lifestyle awareness. Besides bacteria, yeast can be used as a probiotic candidate with specific functional properties. Research on yeast as a probiotic is still limited (except for Saccharomyces boulardii). Previous research has isolated yeasts from the cocoa fermentation process. This study aimed to evaluate the probiotics properties and antioxidant activity of yeast strains isolated from spontaneous cocoa fermentation in Sukabumi, Indonesia. Previous research has isolated 23 yeast strains from spontaneous cocoa (Theobroma cacao L.) fermentation. Of the 23 yeast strains isolated from cocoa fermentation, 22 strains showed negative hemolysis as an indicator of non-pathogenic properties. Ten yeast strains were able to grow at 37 °C and 41 °C, pH 3, 0.5% bile salts, had autoaggregation ability (63.99-95.33%), and co-aggregation with S. typhimurium ATCC14028 (>80%), as character requirement for probiotic candidates. The genetic identification of the ten yeast strains showed that they were 99% identical to Pichia kudriavzevii. Based on its antioxidant activity, the P. kudriavzevii 2P10 metabolites had the highest percentage of inhibition (68.51%) against DPPH free radicals and resistance to H2O2 oxidative stress up to 3 mM. It can be concluded that P. kudriavzevii 2P10 is a promising probiotic candidate for functional foods and health purposes.